COMPARATIVE ANALYSIS OF NATIONAL AND INTERNATIONAL STANDARDS IN COTTON FIBER CLASSIFICATION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
Cotton fiber classification plays a crucial role in determining textile quality, pricing, and international trade competitiveness. This study provides a comparative analysis between the national standard of Uzbekistan (O'z DSt 604:2016) and international cotton classification systems, particularly the USDA and HVI-based standards. The research evaluates differences in impurity content thresholds, grading systems, and technological assessment methods. A comparative analytical approach was applied to identify structural differences in class intervals and contamination limits. The results reveal that while Uzbekistan’s standard primarily emphasizes impurity percentage thresholds, international systems incorporate multi-parameter instrumental evaluation including micronaire, fiber length, strength, color grade, and trash content via High Volume Instrument (HVI) testing. The study highlights the need for harmonization to improve export competitiveness and ensure global market compatibility.